An Analysis Strategies of Translating Song “Lead the Way” Into Indonesian Version Kita Bisa - Tri Andika (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
The aim of this research is to analyse translation strategies utilized in the translation of song “Lead the Way” Into Indonesian Version Kita Bisa. The lines of a pair song lyrics were used as data and the data was limited on the translation of English-Indonesian. The strategy analysis was carried out using the framework developed by Åkerström (2009) and Chesterman (2016). The data in this research was analysed using a qualitative descriptive method. The source and target lines of the lyrics were put side by side in a table. As shown in the result of the research, the translator prefers to translate lyrics lines with fewer words while maintaining the same number of syllables as the original lines. In terms of the translator's strategic translation strategies in translating lines of lyrics, it is found that eight strategies out of thirteen strategies have been used, they are word count, syllables vs words, addition of words, omission of words, metaphor, rhymes, paraphrases, and borrowing strategies.